Feeding plans with the use of glycerin for broilers - Santos, Edna Teles dos; Dourado, Leilane Rocha Barros; Silva, Flávio Ferreira da; de Sousa, Regina Fialho; Lima, Stélio Pinheiro Bezerra de; Siqueira, Jefferson Costa de (Comunicata Scientiae, 2019)
This study aimed to evaluate the effects of feeding plans with or without addition of glycerin, in different ages, on performance, carcass yield, litter moisture and footpad lesions of broiler chickens. 540 male Cobb broilers were utilized, distributed in a completely randomized design with six treatments (treatments consisted of the inclusion or not of glycerin in diets at all periods or only at different stages: 1 to 7, 8 to 21, 22 to 33 and 34 to 42 days), in six replicates of 15 birds each. Diets were provided ad libitum. At 42 days, the average weight, weight gain, feed intake, feed conversion, carcass yield, litter moisture and footpad lesions were evaluated. There was no effect (p> 0.05) of dietary plans on the performance variables. The feeding plans did not influence (p>0,05) the carcass and cuts parameters at 42 days. However, there was significant effect (p <0.05) of the dietary plans on litter moisture and plantar lesions. Effects were observed (p>0,001) for the feeding plans, were the highest and the lowest incidence of lesions were present in the birds that consume diets with and without addition of glycerin, in the period from 1 to 42 days of age, respectively.